An Asymmetric Supercapacitor–Diode (CAPode) for Unidirectional Energy Storage - Zhang, En; Fulik, Natalia; Hao, Guang-Ping; Zhang, Han-Yue; Kaneko, Katsumi; Borchardt, Lars; Brunner, Eike; Kaskel, Stefan (Angewandte Chemie International Edition, 2019)
A new asymmetric capacitor concept is proposed providing high energy storage capacity for only one charging direction. Size-selective microporous carbons (w<0.9 nm) with narrow pore size distribution are demonstrated to exclusively electrosorb small anions (BF4−) but size-exclude larger cations (TBA+ or TPA+), while the counter electrode, an ordered mesoporous carbon (w>2 nm), gives access to both ions. This architecture exclusively charges in one direction with high rectification ratios (RR=12), representing a novel capacitive analogue of semiconductor-based diodes (“CAPode”). By precise pore size control of microporous carbons (0.6 nm, 0.8 nm and 1.0 nm) combined with an ordered mesoporous counter electrode (CMK-3, 4.8 nm) electrolyte cation sieving and unidirectional charging is demonstrated by analyzing the device charge-discharge response and monitoring individual electrodes of the device via in situ NMR spectroscopy.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electroadsorption; ion sieving; iontronics; nanoporous carbon; supercapacitor